Analisis Tingkat Pengungkapan Kinerja Sosial Bank Syariah Berdasarkan Islamic Social Reporting Index - Fatmawati, Rizky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study is to determine the level of social performance disclosure of Bank Syariah Mandiri and Bank Muamalat Indonesia 2016-2018 using the ISR Index model which includes the following six disclosure themes, namely funding and investment, products and services, labor (employees), society and environment and corporate governance. The research method used is qualitative media content analysis or Ethnographic Content Analysis / ECA, which aims to determine the level of social performance disclosure of Islamic banks in Indonesia based on the ISR Index through content analysis of the annual reports of Bank Muamalat Indonesia (BMI) and Bank Syariah Mandiri (BSM). Content analysis is a systematic technique for analyzing message content and processing messages, or a tool for observing and analyzing the content of open communication behavior of selected communicators. Content analysis can be used to analyze newspapers, websites, advertisements, recorded interviews, and company annual reports. From the calculation and analysis of the ISR index in Islamic Banks, that the highest level of social performance disclosure for the 2016-2018 period is Bank Syariah Mandiri. Overall, the level of social performance disclosure of Bank Muamalat Indonesia and Bank Syariah Mandiri in the 2016-2018 period continued to increase every year. While on average in that period the predicate for the level of social performance disclosure of Bank Muamalat Indonesia and Bank Syariah Mandiri was informative